Viral hepatitis in female sex workers using the Respondent-Driven Sampling - Matos,Marcos André de (2017)
ABSTRACT OBJECTIVE To estimate the prevalence of hepatitis B virus and C virus infections and their genotypes and analyze the risk factors for the markers of exposure to hepatitis B virus in female sex workers in a region of intense sex trade. METHODS This is a cross-sectional study performed with four hundred and two female sex workers in Goiânia, Brazil. Data have been collected using the Respondent-Driven Sampling. The women have been interviewed and tested for markers of hepatitis B and C viruses. Positive samples have been genotyped. The data have been analyzed using the Respondent-Driven Sampling Analysis Tool, version 5.3, and Stata 11.0. RESULTS The adjusted prevalence for hepatitis B virus and C virus were 17.1% (95%CI 11.6–23.4) and 0.7% (95%CI 0.1–1.5), respectively. Only 28% (95%CI 21.1–36.4) of the participants had serological evidence of vaccination against hepatitis B virus. Being older (> 40 years), being single, having a history of blood transfusion and use of cocaine, and ignoring the symptoms of sexually transmitted infections were associated with positivity for hepatitis B virus (p < 0.05). We have detected the subgenotype A1 of hepatitis B virus (n = 3) and the subtypes of hepatitis C virus 1a (n = 3) and 1b (n = 1). CONCLUSIONS We can observe a low prevalence of infection of hepatitis B and C viruses in the studied population. However, the findings of the analysis of the risk factors show the need for more investment in prevention programs for sexual and drug-related behavior, as well as more efforts to vaccinate this population against hepatitis B. The genotypes of the hepatitis B virus and C virus identified are consistent with those circulating in Brazil.